Metal–Organic Gels from Silver Nanoclusters with Aggregation‐Induced Emission and Fluorescence‐to‐Phosphorescence Switching - Xie, Zengchun; Sun, Panpan; Wang, Zhi; Li, Hongguang; Yu, Longyue; Sun, Di; Chen, Mengjun; Bi, Yuting; Xin, Xia; Hao, Jingcheng (Angewandte Chemie International Edition, 2020)
Luminescent metal nanoclusters (NCs) are emerging as a new class of functional materials that have rich physicochemical properties and wide potential applications. In recent years, it has been found that some metal NCs undergo aggregation‐induced emission (AIE) and an interesting fluorescence‐to‐phosphorescence (F‐P) switching in solutions. However, insights of both the AIE and the F‐P switching remain largely unknown. Now, gelation of water soluble, atomically precise Ag9 NCs is achieved by the addition of antisolvent. Self‐assembly of Ag9 NCs into entangled fibers was confirmed, during which AIE was observed together with an F‐P switching occurring within a narrow time scale. Structural evaluation indicates the fibers are highly ordered. The self‐assembly of Ag9 NCs and their photoluminescent property are thermally reversible, making the metal–organic gels good candidates for luminescent ratiometric thermometers. Solvent‐induced gelation of Ag nanoclusters with atomic precision has been achieved. The metal–organic gel exhibits aggregation‐induced emission with fluorescence‐to‐phosphorescence switching and reversible changes upon heating‐‐cooling cycles.